Minimize F = (AB)’ + AB’C + AC using Boolean laws.
Answers
Answered by
0
Explanation:
Just use the laws of boolean algebra. Most of the rules are just arithmetic rules but changed a little for binary operation.
Y = A'B'C' + A'B + ABC' + AC
- Y = A'(B'C' +B) + A(BC'+C) (Just factor out the terms like algebra)
Now work on the sub terms (B'C' +B) and (BC' + C) to reduce them.
B'C' + B (using AND distributive law) becomes
(B + B')(B+C') Now (B+B') is simply = 1
Use the same step for the (BC'+C) which becomes (B+C)
NOW..
Y = A'(B+C') + A(B+C)
Y = A'B + A'C' + AB + AC (OR distributive law) (you distribute to see if you can combine and reduce any more terms.)
Y = A'B + AB + A'C' + AC
Y = B(A'+A) + A'C' + AC where (A' + A) = 1
Y = A'C' + AC + B
Similar questions
Math,
2 months ago
Math,
2 months ago
Accountancy,
4 months ago
Economy,
4 months ago
Science,
9 months ago